Will virtual reality be a double-edged sword? Exploring the moderation effects of the expected enjoyment of a destination on travel intention. (June 2019) - Li, Tao; Chen, Yun
Abstract: Although virtual reality (VR) has been found to be more effective in tourism marketing compared to traditional methods, few scholars have explored whether VR has any negative effect on tourism marketing. Based on extrinsic and intrinsic motivation theory, tourists' perceptions of a VR device and VR content are distinguished to explore whether VR could be a double-edged sword. Using a scenario-based questionnaire survey and an experiment, the study found that perceived enjoyment of VR mediates the positive effects of tourists' perceived ease of use and the usefulness of VR on their travel intention. However, the positive relationship is moderated by tourists' expected enjoyment of the destination. When the expected enjoyment of destination is low, higher perceived enjoyment of VR actually leads to lower travel intention. The findings of this study provide evidence that VR will inhibit tourists' travel intention under certain conditions and offer a new perspective for technology-related tourism studies. Highlights: Ease of use and usefulness positively relate to enjoyment of VR and travel intention. Perceived enjoyment of VR has a positive effect on travel intention. The effect of enjoyment of VR is moderated by the expected enjoyment of destination. With high expected enjoyment of the destination, VR experience promotes travel intention. With low expected enjoyment of the destination, VR experience inhibits travel intention.